2020
DOI: 10.3390/ma13173747
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Behaviour of Composite Anodized Layers on Aluminium Alloys

Abstract: Three variants of the micro arc oxidation (MAO) technique have been used to treat a 2017A alloy surface. The first variant was a pure anodized layer, the second an anodized layer with SiC embedded nanoparticles and the third an anodized layer with Si3N4 nanoparticles. Tribological tests were performed for all variants, on three samples for every case. Friction coefficients and wear rates were calculated on the basis of experiments. The pure anodized layer manifested friction coefficient values within the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…As shown in Figure 7(d), the average friction coefficient histogram under different lubrication conditions can be seen more intuitively that the GO–PVA composite film shows better tribological properties on the aluminum alloy sample treated by MAO under the condition of oil lubrication (Arrabal et al. , 2015; Atraszkiewicz et al. , 2020).…”
Section: Resultsmentioning
confidence: 88%
“…As shown in Figure 7(d), the average friction coefficient histogram under different lubrication conditions can be seen more intuitively that the GO–PVA composite film shows better tribological properties on the aluminum alloy sample treated by MAO under the condition of oil lubrication (Arrabal et al. , 2015; Atraszkiewicz et al. , 2020).…”
Section: Resultsmentioning
confidence: 88%
“…[1] However, aluminum also has many disadvantages, such as poor wear resistance, ease of corrosion, [2] and ceramic coating treatment on the surface of aluminum material which can significantly improve its disadvantages. [3] However, as the surface hardness increases, the roughness of the surface will also increase, and the more severe the damage caused to its friction substrate. Frictional wear is one of the main causes of machine parts and machine failure [4,5] and has caused substantial economic losses in the machinery lubrication industry over the past decades because of the effects of wear.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al [21] proved that the incorporation of submicron SiC particles decreased the friction coefficient and wear rate of the MAO coatings prepared on Ti alloy. Radomir et al [22] found that SiC nanoparticles directed affected the nature and intensity of wear during the tribological tests and caused an improvement of the tribological properties of the MAO coating on 2017A aluminium alloy. Chang et al [23] found that the MAO coating on Mg alloy AZ31 in silicate electrolyte with SiC nanoparticles showed an enhanced wear resistance.…”
Section: Introductionmentioning
confidence: 99%